Pinus roxburghii Constituents Augment Human Lymphocytes Mediated Cytotoxicity Towards Cancer Cells - Henok Gullilat (Tabriz University of Medical Sciences, 2021)
Background: Pinus roxburghii has been used in the Himalayan region as folkloric remedy while nothing is yet known about its immunomodulatory potential. Methods: The crude extracts of green and fallen pine needles were subjected to sequential fractionation to get partially purified fractions. Human peripheral blood lymphocytes (PBL)were used to analyze immunoenhancing potential of these fractions. Microcytotoxicity assay was employed to investigate improved cancer cells killing capabilities of PBL against various cancer cell lines. GC-MS was carried out to identify the major compounds in the bioactive fractions. Results: The lymphocyte proliferation assay depicted the immunoenhancing potential of extractsand fractions of fallen and green needles of P. roxburghii. The ethyl acetate fractions of both fallen and green needles displayed highest mitogenic activity on human PBL. Both fractions heightened the expression of cell surface markers (CD3, CD8, and CD56) and significantly increased the production of cytokines (IL-2, IFN-γ and TNF-α). The enhanced intracellular granulysin (immunomarker for activated CTLs and NK cells) expression also confirmed immune stimulatory potential of these fractions on human lymphocytes. The ethyl acetate fractions of pine needles enhanced the cytotoxicity of PBL towards various cancer cells (HCT-116, HeLa, PC-3 and A549) as compared to untreated PBL. GC-MS analysis showed presence of major compounds like 3-α-mannobiose, octakis (trimethylsilyl) ether, methyloxime in ethyl acetate fraction of the green needles and cyclodecasiloxane, eicosamethyl in ethyl acetate fraction of the fallen needles. Conclusion: The bioactive fractions of the fallen and green needles of P. roxburghii stimulate cancer cells killing potential of human lymphocytes.